The return (Hachette Audio, Grand Central Publishing, 2021)
Moving into a family beekeeper cabin to recuperate from war injuries, an Afghanistan veteran falls in love with a guarded sheriff while working with a sullen local teen to investigate the mystery of a grandparent's death.

The last song (Grand Central Pub, 2009)
Seventeen year old Veronica "Ronnie" Miller's life was turned upside-down when her parents divorced and her father--a former concert pianist and teacher--moved from New York City to Wilmington, North Carolina. Three years later, she remains angry and alientated from her parents, especially her father ... until her mother decides it would be in everyone's best interest if she spent the summer in Wilmington with him. An unforgettable story of love on many levels.

The shape of water (Feiwel and Friends, Feiwel & Friends, Macmillan Audio, 2018)
In an otherworldly story set against the backdrop of Cold War-era America, an amphibious man is discovered in the Amazon--and subsequently finds love within the human race.

See me (Blackstone Audio, Inc, Grand Central Publishing, 2015)
"Colin Hancock is giving his second chance his best shot. At 28, he's focused only on walking a straight line - getting his teaching degree, working out at the gym religiously, and avoiding all the places and people that proved so destructive in his earlier life. The last thing he's looking for is a serious relationship. But when Maria Sanchez crosses paths with him on a rain-swept night in North Carolina, his plans are upended in a way that will rattle the foundations of his carefully structured life. As for Maria, the hardworking lawyer and daughter of Mexican immigrants, Colin will challenge every notion she's ever had about herself and her future, making her question what truly makes her happy. Before the couple has a chance to envision what a life together might look like, however, menacing reminders of events in Maria's past begin to surface. And as the threat of violence begins to shadow her every step, she and Colin will be tested in increasingly terrifying ways. Will demons from their past destroy the tentative bonds they have forged, or will their love protect them, even in the darkest hour?" --

The nightingale (St. Martin's Press, Macmillan Audio, Center Point Large Print, 2017)
"From the #1 New York Times bestselling author comes Kristin Hannah's next novel. It is an epic love story and family drama set at the dawn of World War II. She is the author of twenty-one novels. Her previous novels include Home Front, Night Road, Firefly Lane, Fly Away, and Winter Garden"-- "Viann and Isabelle have always been close despite their differences. Younger, bolder sister Isabelle lives in Paris while Viann lives a quiet and content life in the French countryside with her husband Antoine and their daughter. When World War II strikes and Antoine is sent off to fight, Viann and Isabelle's father sends Isabelle to help her older sister cope. As the war progresses, it's not only the sisters' relationship that is tested, but also their strength and their individual senses of right and wrong. With life as they know it changing in unbelievably horrific ways, Viann and Isabelle will find themselves facing frightening situations and responding in ways they never thought possible as bravery and resistance take different forms in each of their actions. Vivid and exquisite in its illumination of a time and place that was filled with great monstrosities, but also great humanity and strength, Kristin Hannah's novel will provoke thought and discussion that will have readers talking long after they turn the last page"-- "With courage, grace, and powerful insight, bestselling author Kristin Hannah captures the epic panorama of World War II and illuminates an intimate part of history seldom seen: the women's war. The Nightingale tells the stories of two sisters, separated by years and experience, by ideals, passion and circumstance, each embarking on her own dangerous path toward survival, love, and freedom in German-occupied, war-torn France--a heartbreakingly beautiful novel that celebrates the resilience of the human spirit and the durability of women. It is a novel for everyone, a novel for a lifetime."--Publisher's description

Two by two (Grand Central Pub, Findaway World, LLC, Hachette Audio, Grand Central Publishing, Grand Central Publishing Large Print, 2016)
"At 32, Russell Green has it all: a stunning wife, a lovable six year-old daughter, a successful career as an advertising executive and an expansive home. He is living the dream, and his marriage to the bewitching Vivian is the center of that. But underneath the shiny surface of this perfect existence, fault lines are beginning to appear, and no one is more surprised than Russ when he finds every aspect of the life he took for granted turned upside down. In a matter of months, Russ finds himself without a job or wife, caring for his young daughter, and struggling to adapt to a new and baffling reality. Throwing himself into the wilderness of single parenting, Russ embarks on a journey at once terrifying and rewarding-- one that will test his abilities and his emotional resources beyond anything he ever imagined"--Goodreads.com.

The wish (Hachette Audio, Grand Central Publishing, [Hachette Audio], 2021)
1996 was the year that changed everything for Maggie Dawes. Sent away at sixteen to live with an aunt she barely knew in Ocracoke, a remote village on North Carolina’s Outer Banks, she could think only of the friends and family she left behind . . . until she meets Bryce Trickett, one of the few teenagers on the island. Handsome, genuine, and newly admitted to West Point, Bryce gradually shows her how much there is to love about the wind-swept beach town—and introduces her to photography, a passion that will define the rest of her life. By 2019, Maggie is a renowned travel photographer. She splits her time between running a successful gallery in New York and photographing remote locations around the world. But this year she is unexpectedly grounded over Christmas, struggling to come to terms with a sobering medical diagnosis. Increasingly dependent on a young assistant, she finds herself becoming close to him. As they count down the last days of the season together, she begins to tell him the story of another Christmas, decades earlier—and the love that set her on a course she never could have imagined...$c Provided by publisher.

The last promise (Dutton, Wheeler Pub, 2003)
Having followed her new husband to his native home in rustic Tuscany, Ellana distracts herself from her marital disappointments by caring for her asthmatic son, and reevaluates her life when she meets American art lover Ross Story.

Still me (Me Before You, 3,, 2018)
Louisa Clark arrives in New York ready to start a new life, confident that she can embrace this new adventure and keep her relationship with Ambulance Sam alive across several thousand miles. She is thrown into the world of the superrich Gopniks: Leonard and his much younger second wife, Agnes, and a never-ending array of household staff and hangers-on. Lou is determined to get the most out of the experience and throws herself into her job and New York life within this privileged world.

The city: a novel (Thorndike Press large print core, ,, 2014)
"#1 New York Times bestselling author Dean Koontz is at the peak of his acclaimed powers with this major new novel. The city changed my life and showed me that the world is deeply mysterious. I need to tell you about her and some terrible things and wonderful things and amazing things that happened. and how I am still haunted by them. Including one night when I died and woke and lived again. Here is the riveting, soul-stirring story of Jonah Kirk, son of an exceptional singer, grandson of a formidable "piano man," a musical prodigy beginning to explore his own gifts when he crosses a group of extremely dangerous people, with shattering consequences. Set in a more innocent time not so long ago, The City encompasses a lifetime but unfolds over three extraordinary, heart-racing years of tribulation and triumph, in which Jonah first grasps the electrifying power of music and art, of enduring friendship, of everyday heroes. The unforgettable saga of a young man coming of age within a remarkable family, and a shimmering portrait of the world that shaped him, The City is a novel that speaks to everyone, a dazzling realization of the evergreen dreams we all share. Brilliantly illumined by magic dark and light, it's a place where enchantment and malice entwine, courage and honor are found in the most unexpected quarters, and the way forward lies buried deep inside the heart. Acclaim for Dean Koontz "A rarity among bestselling writers, Koontz continues to pursue new ways of telling stories, never content with repeating himself."--Chicago Sun-Times "Tumbling, hallucinogenic prose. 'Serious' writers. might do well to examine his technique."--The New York Times Book Review "[Koontz] has always had near-Dickensian powers of description, and an ability to yank us from one page to the next that few novelists can match."--Los Angeles Times "Koontz is a superb plotter and wordsmith. He chronicles the hopes and fears of our time in broad strokes and fine detail, using popular fiction to explore the human condition."--USA Today "Characters and the search for meaning, exquisitely crafted, are the soul of [Koontz's] work. One of the master storytellers of this or any age."--The Tampa Tribune "A literary juggler."--The Times (London)"-- "There are millions of stories in the city--some magical, some tragic, others terror-filled or triumphant. Jonah Kirk's story is all of those things as he draws readers into his life in the city as a young boy, introducing his indomitable grandfather, also a "piano man;" his single mother, a struggling singer; and the heroes, villains, and everyday saints and sinners who make up the fabric of the metropolis in which they live--and who will change the course of Jonah's life forever. Welcome to The City, a place of evergreen dreams where enchantment and malice entwine, where courage and honor are found in the most unexpected corners and the way forward lies buried deep inside the heart"--

Fourth wing (Empyrean, 1,, 2023)
"Twenty-year-old Violet Sorrengail was supposed to enter the Scribe Quadrant, living a quiet life among books and history. Now, the commanding general--also known as her tough-as-talons mother--has ordered Violet to join the hundreds of candidates striving to become the elite of Navarre: dragon riders. But when you're smaller than everyone else and your body is brittle, death is only a heartbeat away ... because dragons don't bond to 'fragile' humans. They incinerate them. With fewer dragons willing to bond than cadets, most would kill Violet to better their own chances of success. The rest would kill her just for being her mother's daughter--like Xaden Riorson, the most powerful and ruthless wingleader in the Riders Quadrant. She'll need every edge her wits can give her just to see the next sunrise. Yet, with every day that passes, the war outside grows more deadly, the kingdom's protective wards are failing, and the death toll continues to rise. Even worse, Violet begins to suspect leadership is hiding a terrible secret"--Provided by publisher

Every breath (Hachette Audio, Grand Central Publishing, 2018)
A chance encounter becomes a transcendent turning point for two very different people--the conflicted daughter of an ALS patient and a Sunset Beach newcomer from Zimbabwe who aims to meet his birth father.